Cognitive and Neural Effects of Vision‐Based Speed‐of‐Processing Training in Older Adults with Amnestic Mild Cognitive Impairment: A Pilot Study. Issue 6 (June 2016) - Lin, Feng; Heffner, Kathi L.; Ren, Ping; Tivarus, Madalina E.; Brasch, Judith; Chen, Ding‐Geng; Mapstone, Mark; Porsteinsson, Anton P.; Tadin, Duje
Abstract : Objectives: To examine the cognitive and neural effects of vision‐based speed‐of‐processing (VSOP) training in older adults with amnestic mild cognitive impairment (aMCI) and contrast those effects with an active control (mental leisure activities (MLA)). Design: Randomized single‐blind controlled pilot trial. Setting: Academic medical center. Participants: Individuals with aMCI (N = 21). Intervention: Six‐week computerized VSOP training. Measurements: Multiple cognitive processing measures, instrumental activities of daily living (IADLs), and two resting state neural networks regulating cognitive processing: central executive network (CEN) and default mode network (DMN). Results: VSOP training led to significantly greater improvements in trained (processing speed and attention: F 1, 19  = 6.61, partial η 2  = 0.26, P  = .02) and untrained (working memory: F 1, 19  = 7.33, partial η 2  = 0.28, P  = .01; IADLs: F 1, 19  = 5.16, partial η 2  = 0.21, P  = .03) cognitive domains than MLA and protective maintenance in DMN ( F 1, 9  = 14.63, partial η 2  = 0.62, P  = .004). VSOP training, but not MLA, resulted in a significant improvement in CEN connectivity ( Z  = −2.37, P  = .02). Conclusion: Target and transfer effects of VSOP training were identified, and links between VSOP training and two neural networks associated with aMCI were found. These findings highlight the potential of VSOP training to slow cognitive decline in individuals with aMCI. Further delineation of mechanisms underlying VSOP‐induced plasticity is necessary to understand in which populations and under what conditions such training may be most effective.